KRIS NUSANTARA: KRIS AS A BOND OF SOCIO-CULTURAL VALUES SHIFTS INTO INDIVIDUAL-CULTURAL BONDS AND AS ASSETS IN BUSINESS ALTERNATIVES - Dharsono Dharsono, M.Sn (ARTISTIC : International Journal of Creation and Innovation, 2020)
Kris as an artifact is an expression of community culture in the form of artifacts as the result of ideas and human behavior in the community (in this case Javanese society). Kris which was originally used as a bond in socio-cultural values turned into individual-cultural bonds that could be used as assets in business alternatives. To reach the objectives, the steps of research that are carried out with a qualitative research model with a cultural approach are needed, referring to the teachings of Javanese culture in accordance with the philosophy of Javanese culture. This research produces preservation kris, which is stored and treated as one of the culture of kelangenan, as a cultural heritage, and in conservation, namely conservation by trying to develop values in accordance with the social institutions of the community. Kris as a national cultural asset leads to a conservation-progressive force. The tough kris that develops in the kris community is revitalizing conservation (sanggit), vitally still referring to traditional art as its main reference. Kris in the latest development has become a trend in the development of the art business.